Genotoxic activity and toxicity of Baccharis trimera Less. regarding the bioaccumulation of heavy metals - Silva, Regildo Márcio Gonçalves da [UNESP]; Oliveira, Vanessa Marques de [UNESP]; Valadares, Fillipi [UNESP]; Mecina, Gustavo Franciscatti [UNESP]; Silva, Luciana Pereira [UNESP] (My University, 2012)
Baccharis trimera Less. (“carqueja”) is a native plant from Brazil, used in folk medicine preparations such as infusions and/or decoctions. The objective of this study was to evaluate the toxicity and genotoxicity of aqueous and ethanolic extracts of B. trimera and quantify heavy metals bioaccumulated in this specie. The extracts were prepared with ultra pure water. The Allium cepa test was conducted to examine the genotoxic activity of the extracts. The toxicological activity was used as bioassay of Artemia salina. Heavy metals were analyzed by atomic absorption spectrophotometery. The ethanolic extract showed the greatest effect on the mitotic index and chromosomal aberrations when treated with aqueous extract. The extracts showed activity in the toxicological concentrations. Heavy metals analyzed (Cd = 0.013, Cu = 0.089, Pb = 0.097 and Zn = 1.918 μg/ml) were measured at levels above those recommended. Therefore, B. trimera is a heavy metal bioacumulator specie, being able to promote genotoxicity activity in meristematic cells of A. cepa and toxicological activity on larvae of A. salina.
Keywords: Allium cepa; Artemia salina; Atomic absorption; Chromosome aberration; Genotoxicity; Micronucleus